Territorialidade e ancestralidade: formação e reconhecimento da comunidade pescadora extrativista do Quilombo do Degredo, Brasil - Lorena Lins; Augusto Cesar Salomão Mozine (Revista de Estudios Sociales)
This article explores the interplay between ancestry and territoriality in the formation and formal recognition of the quilombola fishing and extractive community of Degredo, Brazil. Using participant observation, focus groups, and interviews conducted between 2018 and 2021, the study examines how community members perceive their identity and territoriality, and how these factors influenced the recognition process. The Degredo community faces daily challenges, including interference from exploitative enterprises and conflicts with regional farmers. Deeply connected to the sea, rivers, and lagoons—essential spaces for family life and collective activities—the community frequently engages in environmental licensing processes characterized by limited dialogue and minimal participation. They also confront broader issues such as road construction projects, backyard pipelines, inadequate infrastructure, and restricted access to social rights, including education, healthcare, transportation, housing, employment, and income. In response to these adversities, the Degredo quilombola community has fostered strong collective mobilization to defend their territorial rights and maintain their way of life, which in turn shapes their unique identity and territoriality. The 2015 collapse of the Fundão dam, owned by the Samarco mining company in Mariana, Minas Gerais, Brazil, exacerbated these challenges. By February 2016, mining tailings carried by the wind had reached Degredo beach, further affecting the community. Drawing on critical political ecology, this article highlights how Degredo contends with agricultural and industrial exploitation projects while addressing long-standing socio-environmental conflicts. The study also delves into the community’s process of self-determination and its formal recognition as a quilombola by Brazil’s National Agrarian Reform Institute and the Palmares Cultural Foundation.